Diction Associative Meaning: The Case of Men and Women Face Wash Products in Indonesia - Riani, Riri Rachmah; Hidayat, Didin Nuruddin; Alek, Alek (Universitas Lancang Kuning, 2021)
This research discusses the associative meaning of dictions in face wash products for men and women. The study focuses on the use of different dictions displayed in the product description of face wash products. The descriptions of 60 face wash products, 30 for men and 30 for women, were collected. The approach used in this research is semantic analysis. This research aims to discover the associative meanings which occur in the dictions and to find out whether they correspond with the consumer’s point of view. The result shows that the dictions used for face wash products for women give an impression of beauty for the female facial skin, such as lovely, sparkling, flawless, and pearly. On the other hand, the dictions for men’s products give an impression of strengths, such as fighter, buster, energy, and active. This leads to the conclusion that the dictions in face wash products for women are related to ideal physical characteristics of female skin. As for men’s products, the dictions are related to general characteristics of being an active man.